The Relationship Between Family Support and Medication Compliance of Elderly Hypertension Patients at Durenan Community Health Center - Neni Probosiwi (Parapemikir : Jurnal Ilmiah Farmasi, 2025)
Hypertension increases with age, especially in the elderly. This study aims to determine the relationship between family support and medication adherence in elderly patients with hypertension in the outpatient unit of the Durenan Community Health Center. This study is a non-experimental, prospective, observational quantitative study with descriptive analysis. The sample consisted of 98 elderly respondents selected using purposive sampling. Primary data were obtained from the Perceived Social Support Questionnaire Family (PSS-Fa) to assess family support and the Adherence to Refills and Medications Scale-Short Form (ARMS-SF) to assess adherence. Secondary data were obtained from patient medical records. The results showed that of the 54 respondents with good family support, 51 respondents were compliant and 3 were non-compliant. Conversely, of the 44 respondents with poor family support, only 7 were compliant and 37 were non-compliant. The chi-square test showed a p-value of 0.000 (p 0.05), which means there is a significant relationship between family support and medication adherence. A correlation coefficient (CC) of 0.982 indicates a very strong relationship, meaning that the better the family support, the higher the medication adherence in hypertension patients. Family support has been shown to be a crucial factor in the success of hypertension therapy in the elderly.